Role of empowering leadership in improving faculty engagement and motivation in higher education institutions - Sharish Abdullah; Riffat-un-Nisa Awan; Abida Parveen; Zunaira Fatima; Ghazanfar Ali (Institute of Advanced Engineering and Science, 2026)
Higher education institutions face challenges in maintaining faculty motivation and engagement. Leadership empowerment is usually perceived as an important factor in fostering employee outcomes. This study intended to examine the effect of leadership empowerment on employee engagement and motivation at higher education levels. It was a quantitative study and a survey was used to collect data. The questionnaire consisted of 59 items, regarding three variables i.e., leadership empowerment (leading by example, participative decision-making, coaching, informing, and interaction with team), motivation (intrinsic motivation and extrinsic motivation), and employee engagement (affective engagement, intellectual engagement). Data were collected from a sample of 200 teachers (130 males, 70 females) from the University of Sargodha. The data was analyzed using Pearson correlation and regression analysis. The study concluded that leadership empowerment significantly affected employee engagement and motivation. Leading by example significantly affected intellectual and affective engagement and both intrinsic and extrinsic motivation, whereas only participative decision-making affected extrinsic motivation. It is suggested that leaders should create a supportive and empowering environment by setting examples, recognizing efforts, and providing growth opportunities. They should empower employees to feel valued and motivated to contribute to the organization’s success.